Divination on stage : prophetic body signs in early modern theatre in Spain and Europe - Gernert, Folke (Walter de Gruyter GmbH, 2021)
Magicians, necromancers and astrologers are assiduous characters in the European golden age theatre. This book deals with dramatic characters who act as physiognomists or palm readers in the fictional world and analyses the fictionalisation of physiognomic lore as a practice of divination in early modern Romance theatre from Pietro Aretino and Giordano Bruno to Lope de Vega, Calderón de la Barca and Thomas Corneille.